The effect of acute exercise on glycogen synthesis rate in obese subjects studied by 13C MRS - van der Graaf, Marinette; de Haan, Jacco H.; Smits, Paul; Mulder, Alexandra H.; Heerschap, Arend; Tack, Cees J. (European journal of applied physiology, 2011)
In obesity, insulin-stimulated glucose uptake in skeletal muscle is decreased. We investigated whether the stimulatory effect of acute exercise on glucose uptake and subsequent glycogen synthesis was normal. The study was performed on 18 healthy volunteers, 9 obese (BMI = 32.6 ± 1.2 kg/m 2 , mean ± SEM) and 9 lean (BMI = 22.0 ± 0.9 kg/m 2 ), matched for age and gender. All participants underwent a euglycemic hyperinsulinemic clamp, showing reduced glucose uptake in the obese group ( P = 0.01), during which they performed a short intense local exercise (single-legged toe lifting). Dynamic glucose incorporation into glycogen in the gastrocnemius muscle before and after exercise was assessed by 13 C magnetic resonance spectroscopy combined with infusion of [1- 13 C]glucose. Blood flow was measured to investigate its potential contribution to glucose uptake. Before exercise, glycogen synthesis rate tended to be lower in obese subjects compared with lean (78 ± 14 vs. 132 ± 24 μmol/kg muscle/min; P = 0.07). Exercise induced highly significant rises in glycogen synthesis rates in both groups, but the increase in obese subjects was reduced compared with lean (112 ± 15 vs. 186 ± 27 μmol/kg muscle/min; P = 0.03), although the relative increase was similar (184 ± 35 vs. 202 ± 51%; P = 0.78). After exercise, blood flow increased equally in both groups, without a temporal relationship with the rate of glycogen synthesis. In conclusion, this study shows a stimulatory effect of a short bout of acute exercise on insulin-induced glycogen synthesis rate that is reduced in absolute values but similar in percentages in obese subjects. These results suggest a shared pathway between insulin- and exercise-induced glucose uptake and subsequent glycogen synthesis.